Function and structure relationships of a β‐1, 2‐glucooligosaccharide‐degrading β‐glucosidase. Issue 23 (24th November 2017) - Ishiguro, Rikuto; Tanaka, Nobukiyo; Abe, Koichi; Nakajima, Masahiro; Maeda, Takuma; Miyanaga, Akimasa; Takahashi, Yuta; Sugimoto, Naohisa; Nakai, Hiroyuki; Taguchi, Hayao
Abstract : BT_3567 protein, a putative β‐glucosidase from Bacteroides thetaiotaomicron, exhibits higher activity toward Sop3–5 (Sopn, n: degree of polymerization of β‐1, 2‐glucooligosaccharides) than toward Sop2, unlike a known β‐glucosidase from Listeria innocua which predominantly prefers Sop2 . In the complex structure determined by soaking of a D286N mutant crystal with Sop4, a Sop3 moiety was observed at subsites −1 to +2. The glucose moiety at subsite +2 forms a hydrogen bond with Asn81, which is replaced with Gly in the L. innocua β‐glucosidase. The K m values of the N81G mutant for Sop3–5 are much higher than those of the wild‐type, suggesting that Asn81 contributes to the binding to substrates longer than Sop3 . Abstract :